Caracterización de nueve agroecosistemas de café de la cuenca del río Porce, Colombia, con un enfoque agroecológico (2015)
ABSTRACT: The purpose of this paper is to characterize nine coffee agroecosystems from the Colombian Andes with an agroecological approach. Attributes and indicators evaluated are grouped under three dimensions: economic, social and technical-productive. Indicators are sensitive to agroecosystem conditions and can be easily understood by farmers. Low productivity of coffee plantations and economic risk are identified as the main problems. The study found high food security in most of the farms despite deficiencies in coffee productivity. The methodology proposed could be adapted by other researchers for the characterization of peasant agroecosystems without forgetting that setting indicators should be a participatory process; indicators used in this work do not account for all internal and external conditions that affect agroecosystems but they highlight relevant factors for social reproduction of peasant families.